Current pharmacotherapy of antineoplastic-induced nausea and vomiting (Research, Society and Development, 2021)
Chemotherapy-induced nausea and vomiting (CINV) are common adverse drug reactions with the use of anticancer drugs. Although there are advances in prophylactic therapy, the management of antiemetic drugs in clinical practice is still a challenge to be faced. The aim of this study was to search the scientific literature for the main pharmacological therapies used in this condition. A systematic review was carried out, in which scientific articles indexed in PubMed, ScienseDirect and Web of Science were searched, using the following descriptors: chemotherapy; nausea; vomiting; drug therapy; serotonin 5-HT3 receptor antagonists, neurokinin-1 receptor antagonist. The degree of emetogenicity is increased by antineoplastic agents directly in the treatment of CINV, which include serotonin (5-HT3) receptor antagonists, neurokinin (NK-1) receptor antagonists. This treatment can be done individually, however, if it is not responsive, it is possible to make the association between these two classes. In more complicated cases, triple therapy is indicated, consisting of a combination of 5-HT3 receptor antagonists with NK-1 and dexamethasone receptor antagonists. Therefore, an efficacy of antiemetic therapy is increased in this triad when compared to drug treatment individually. First-generation 5-HT3 receptor antagonists are very effective, however, second-generation palonosetron is more effective and safer. A portion of netupitant and palonosetron, when given together with a dexamethasone, has been a good option for the treatment of CINV.